Analisis Penggunaan Fashion Androgini Sebagai Media Komunikasi di Kota Denpasar - Perkasa, Syahdad; Sugiarica Joni, I Dewa Ayu; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
Androgynous fashion can be said as a non-verbal communication medium because it does not use oral or written words in the delivery of the message. Where the elements contained in androgynous fashion such as clothing, hairstyles, and accessories worn by androgynous fashion users consciously or unconsciously can convey a message of emotion, feelings, behavior, or personality of the user. The purpose of this study is to find out what messages to be conveyed by users of androgynous fashion and how androgynous fashion is used as a medium to communicate. Data collection was done by observation method, interview and documentation study. This research is a qualitative research with explorative study method. The analysis technique that used in this research is interactive model analysis, Milles and Huberman. The results of this study is to show that androgynous fashion is not only used as a medium to convey a message of emotion, feelings, behavior or personality of the user, but also used to express themselves and distinguish someone with others, both in terms of the profession, hobbies and interest. Androgynous fashion is also a form of self-liberation from the gender barriers and social constructs that exist in society. In addition, androgynous fashion is also used as an effort to communicate social class status in the society.   Keywords : Androgynous Fashion, Medium of Communication, Non-verbal, Message.